Solution and Solid State Study of Nickel(II) Ternary Complexes Containing 5-Aminolevulinic Acid Drug and Amino Acids - Al-Qahtani, Salhah D. (Asian Journal of Chemistry, 2020)
Solution equilibria of the systems Ni(II)-5-aminolevulinic acid as ligand (A) and the amino acids [alanine (Ala), valine (Val), methylamine (Met), imidazole (Imi), Histidine (His), serine (Ser), cysteine (Cys) and penicillamine (Pen)] as ligands (L) have been studied pH-metrically. The stability constants of mixed ligand complexes were calculated with I = 0.10 mol L-1 KNO3 using HYPERQUAD program at 25 ± 0.1 ºC. The log10 X values showed a higher stabilities for the mixed ligand complexes compared to the binary analogues. The synthesis and characterization of the new amino acid mononuclear Ni(II) binary complex [NiA] (1) and ternary complex [NiAL] (2) were achieved via molar conductance, elemental analysis UV-vis, IR, 1H NMR, thermal analysis and magnetic moment. The thermogravimetric analysis of complexes were investigated by TG-DTA suggests that the complexes possess high thermal stability formation and their respective nickel oxide for 1 and nickel sulfide for 2 as final chemical entities, which are thermally stable. The nickel(II) chelates were found to be non-electrolytes, diamagnetic moments and the geometry around Ni(II) ion in complexes 1 and 2 is square planar.